PENGARUH PEMIKIRAN ULAMA SUMATERA SELATAN ABAD XX TERHADAP DINAMIKA DAN PRODUKTIVITAS MASYARAKAT SUMATERA SELATAN - Nurseri Hasnah Nasution (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
In the twentieth century, South Sumatra was characterized by the religious phenomenon of postmodernism and the problems of religious articulation diversity. To respond to these phenomena and problems, some South Sumatra clerics such as K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry formulated thoughts. Subject matter of theocentric theological thought K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry consists of: the position of reason, the function of revelation, the concept of faith, human actions, anthropomorphism, beatific vision, the attributes of God, the deeds of God, the power of God, the justice and the word of God. Thought K.H. Anwar Kumpul, K.H. M. Zen Syukri, K.H. Zainal Abidin Fikry is traditional. However, their thinking has an effect on the dynamics and productivity of the people of South Sumatra. This study deconstructs the collective perceptions and memories introduced by Harun Nasution. It conjures that traditional theology is the cause of stagnation.